TIPOLOGI EPISTEMOLOGI HUKUM ISLAM (Analisis Metode Penetapan Awal Bulan Hijriyah Tokoh-tokoh Agama Tulungagung) - Musonnif, Ahmad (Ahkam: Jurnal Hukum Islam, 2019)
ABSTRACTThe epistemological features of Islamic Law increasingly vary along with the development of Islam. This is due to the interaction of the Muslims’ thinking with the development of new scientific and epistemological patterns developed at the new locus of Muslims. The focus of this research is analyzing the Islamic law epistemology of the Tulungagung religious leaders in the initial determination of the Islamic month. The research method used is interview and observation, and literature search. The analysis is then carried out with the epistemological approach of Islam. From the perspective of legal epistemology, Tulungagung religious leaders fluent in four epistemological categories, namely Bayani, Burhani, and Irfani, similar to the typology introduced by al-Jabiri. In addition, there are other epistemological features, namely taqli di-Ittiba'i, which are very close to the Sufism tradition.Keywords: Islamic Legal Epitemology, Tulungagung Religious Leaders, Determination of HijriCalendar.